Onshore power one option to reduce air emissions in ports - Iven Krämer; Ernest Czermański (Sustainability Management Forum, 2020)
Ports are not just nodal points in global supply chains but at the same time, they are concentration points for air emissions. Ships that are manoeuvring within estuaries and within the port areas and ships at berth contribute to a~large extend to the overall air pollution in port cities. Thus, the efforts to reduce these emissions are not only left to the shipping lines themselves, but to port authorities, port operators and port cities as well. One option that lately has gained huge political interest is onshore power supply. Consequently, more and more ports in the world begin to plan and implement such installations. For the time being, this process is yet in an initial phase and even if different technical solutions do exist and prove their usability in daily operations, the needed investments for the installations do barely see any economic viability. The same is to observe for the operational costs, which is why a~discussion for a~general obligation to use shore power in ports is ongoing. Time will show if shore power really is a~solution or if shipping lines will find even better options to reduce air emissions on their path towards a~zero emission shipping.
Keywords: 650; Green shipping; Green-ports onshore Power Supply; Electrification of ports; Air emissions